Al-Shāfi’ī’s Perception of Taḥrīf and its Implications for Muslim-Christian Relations in Marsabit County, Kenya (Impact: Journal of Transformation, 2023)
This paper examines the knowledge that Muslim teachers in Marsabit have on taḥrīf and its effects on Muslim-Christian relations in the area. Muhammad acknowledged Judaism and Christianity as monotheistic religions and their scriptures as revelations from God. However, Muslim scholars later claimed a deviation of these scriptures from the “original ones”, a teaching known in Arabic as taḥrīf. Taḥrīf is a severe accusation against Jews and Christians as untrustworthy, and their respective faiths as an adulteration. In this paper, Jews refers to those who follow Judaism. Taḥrīf is examined, based on the the Qur’an and the Hadith as interpreted in the Shāfiʽī school of Islamic law that dominates in East Africa. Teachings by Abū Abdullāh Muhammad Ibn Idrīs Al-Shāfiʽī, the founder of the school, and Ibn Kathir, a famous Shāfiʽī scholar, have then been compared with those of Marsabit Muslim teachers. This document is based on research conducted in Marsabit between 2019 and 2021 where ten Muslim teachers were interviewed. The research finds that taḥrif is perpetuated in Marsabit ideological Muslims, which impacts negatively on both the ideological and ordinary level of relationships between Muslims and Christians. Ideas from ‘affect regulatory theory’ have been used to explain effects of taḥrīf on the Muslim-Christian relations. Active dialogue between teachers of the two religions is proposed to address challenges arising from taḥrīf towards promoting dyadic and inter-group relations in Marsabit.